Surface modification of malachite with ethanediamine and its effect on sulfidization flotation - Feng, Qicheng; Zhao, Wenjuan; Wen, Shuming (Applied surface science, 2018)
[Display omitted] •Ethanediamine modification of malachite improved its sulfidization and flotation behaviors.•Ethanediamine modification of malachite enhanced the reactivity of sulfidized mineral surfaces.•More Cu(II) species on sulfidized malachite surfaces were reduced to Cu(I) species after modification.•The percentages of S22− and Sn2− relative to the total S on sulfidized mineral surfaces increased after modification. Ethanediamine was used to modify the mineral surface of malachite to improve its sulfidization and flotation behavior. The activation mechanism was investigated by adsorption experiments, X-ray photoelectron spectroscopy (XPS) analysis, and zeta potential measurements. Microflotation experiments showed that the flotation recovery of malachite was enhanced after the pretreatment of the mineral particles with ethanediamine prior to the addition of Na2S. Adsorption tests revealed that numerous sulfide ion species in the pulp solution were transferred onto the mineral surface through the formation of more copper sulfide species. This finding was confirmed by the results of the XPS measurements. Ethanediamine modification not only increased the contents of copper sulfide species on the malachite surface but also enhanced the reactivity of the sulfidization products. During sulfidization, Cu(II) species on the mineral surface were reduced into Cu(I) species, and the percentages of S22− and Sn2− relative to the total S increased after modification, resulting in increased surface hydrophobicity. The results of zeta potential measurements showed that the ethanediamine-modified mineral surface adsorbed with more sulfide ion species was advantageous to the attachment of xanthate species, thereby improving malachite floatability. The proposed ethanediamine modification followed by sulfidization xanthate flotation exhibits potential for industrial application.